A study of enhanced structural, microstructural and dielectric behaviour of aliovalent ions doped BaZr0.05Ti0.95O3 ceramic. Issue 1 (March 2021) - Nag Bhargavi, G; Badapanda, Tanmaya; Khare, Ayush; Shahid Anwar, M
Abstract: The lead-free ceramics are considered to be the best substitutes for lead based ceramics which have tremendous harmful effects regarding environmental pollution. In this concern, the lead-free ceramics have been widely attracted by research communities. In the present study we have prepared lead free BaZr0.05 Ti0.95 O3 perovskite ceramics with various doping concentrations of Gd 3+ ions by the conventional solid-state reaction method. The perovskite phase formation was studied by x-ray diffraction which indicate the transformation of crystal symmetry from orthorhombic to tetragonal structure for the Gd 3+ ions doped samples. The scanning electron microscopy studies revealed the modification in grain size on doping Gd ions also the energy dispersive X-ray spectra have been obtained to study the compositional variations. The dielectric and loss studies have been performed in the large range of temperature and frequency. The low dielectric loss and high dielectric constant suggests possible applications in memory devices and ceramic capacitors. Temperature coefficient of capacitance plots have also been plotted.